Judgment and classification of emotion terms by older and younger adults. (3rd July 2017) - Ready, Rebecca E.; Santorelli, Gennarina D.; Mather, Molly A.
ABSTRACT: Objectives : Theoretical models of adult development suggest changes in emotion systems with age. This study determined how younger and older adults judged and classified 70 emotion terms that varied in valence and arousal, and that have been used in previous studies of adult aging and emotion. The terms were from the Positive and Negative Affect Schedule – Expanded (PANAS-X) and the (KS) affect scales. Method : Older ( n = 32) and younger adults ( n = 111) engaged in a card sort task which determined how the 70 emotion terms were classified (i.e. grouped) in relation to one another. Activation and valence ratings of emotion terms were collected. Results : There were 17 age group differences in item ratings for activation and 19 for valence. Older adults tended to rate emotion terms and scales as more positive and activating than younger persons. Card sort data indicated similarity in conceptualizations of emotion terms across groups with exceptions for serene, sad, and lonely . Conclusions : Research that utilizes self-report emotion data from older and younger persons should consider how perceptions of emotion terms may vary systematically with age. The constructs of sadness, loneliness, and serene may be age-variant and necessitate age-based adjustments in assessment and intervention. Further, older adults may perceive some emotion terms to be more activating and positive than younger persons.